2021
DOI: 10.3390/cells10051033
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Non-IgE-Mediated Pseudo-Allergic Reaction Puzzle with Mas-Related G-Protein Coupled Receptor Member X2 (MRGPRX2)

Abstract: Mas-related G-protein coupled receptor member X2 (MRGPRX2) is a class A GPCR expressed on mast cells. Mast cells are granulated tissue-resident cells known for host cell response, allergic response, and vascular homeostasis. Immunoglobulin E receptor (FcεRI)-mediated mast cell activation is a well-studied and recognized mechanism of allergy and hypersensitivity reactions. However, non-IgE-mediated mast cell activation is less explored and is not well recognized. After decades of uncertainty, MRGPRX2 was discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 197 publications
(365 reference statements)
0
73
0
1
Order By: Relevance
“…Also, in an “immuno-active” group of IBS patients, genes coding for the pro-inflammatory cytokine IL-1β and mast cell G-protein coupled receptor MRGPRX2, as well as the cyclooxygenase gene PTGS2 were significantly upregulated in the colon compared to healthy controls ( Aguilera-Lizarraga et al, 2019 ). All of these have been implicated in mast cell activation ( Aguilera-Lizarraga et al, 2019 ), with MRGPRX2 in specific mediating IgE-independent mast cell activation in response to various ligands including eosinophil cationic proteins ( Ali, 2016 ; Kumar et al, 2021 ).…”
Section: Factors Related To Immune Activationmentioning
confidence: 99%
“…Also, in an “immuno-active” group of IBS patients, genes coding for the pro-inflammatory cytokine IL-1β and mast cell G-protein coupled receptor MRGPRX2, as well as the cyclooxygenase gene PTGS2 were significantly upregulated in the colon compared to healthy controls ( Aguilera-Lizarraga et al, 2019 ). All of these have been implicated in mast cell activation ( Aguilera-Lizarraga et al, 2019 ), with MRGPRX2 in specific mediating IgE-independent mast cell activation in response to various ligands including eosinophil cationic proteins ( Ali, 2016 ; Kumar et al, 2021 ).…”
Section: Factors Related To Immune Activationmentioning
confidence: 99%
“…Since 85% of the patients who had pseudoallergic reactions to neuromuscular blocking agents were not previously treated with neuromuscular blocking agents [ 127 ], IgE-independent MC activation by neuromuscular blocking agents may be a factor causing pseudoallergic reactions. It has been reported that the pseudo-allergic reactions to several FDA-approved drugs were from MRGPRX2-mediated MC activation [ 20 , 128 , 129 ]. Subsequently, clozapine, an antipsychotic drug, and codeine have been reported to cause pseudoallergic reactions via MRGPRX2 [ 54 , 130 ].…”
Section: Drug-induced Pseudoallergic Reactionmentioning
confidence: 99%
“…With the discovery of Mas-related G protein-coupled receptor member X2 (MRGPRX2) as a key receptor of IgE-independent mast cell (MC) degranulation, two similarly effective routes of degranulation are now established in skin MCs [1,2]. The presumed clinical significance of MRGPRX2 stems from the plethora of ligands, both endogenous and exogenous, that reportedly activate the receptor [1,[3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%